2020
DOI: 10.1016/j.wombi.2019.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Midwifery Student Evaluation of Practice: The MidSTEP tool — Perceptions of clinical learning experiences

Abstract: BackgroundLittle emphasis has been given to the standardised measurement of midwifery students' perceptions of their clinical learning experiences. AimTo develop a tool that evaluates students' perceptions of their clinical learning experiences according to environment and impact of preceptors on professional development. MethodsA cross-sectional design was used. Tool development had three phases: item generation; expert review to assess clarity, apparent internal consistency and content validity; and psychome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 39 publications
(48 reference statements)
0
17
0
4
Order By: Relevance
“…There is a need to define the factors that influence student-mentor relationships, as well as ways in which to establish and maintain trusting and supportive partnerships between students and midwives. The development of tools that allow evaluation of learning from placement experiences, such as that recently devised by Griffith et al 44 may assist in this.…”
Section: Student-mentor Relationshipsmentioning
confidence: 99%
“…There is a need to define the factors that influence student-mentor relationships, as well as ways in which to establish and maintain trusting and supportive partnerships between students and midwives. The development of tools that allow evaluation of learning from placement experiences, such as that recently devised by Griffith et al 44 may assist in this.…”
Section: Student-mentor Relationshipsmentioning
confidence: 99%
“…These characteristics were comparable to three of the four key accountabilities of Griffith Midwifery Academic role identified above. While most roles described in the literature were available to students and mentors on an ad hoc basis for indirect support, Midwifery Academics at Griffith University are assigned to one or more partner healthcare organisation sites, attending on specified days of the week, and working to strengthen clinical-university partnerships as part of their employment role responsibilities 13 . What was less clear was the extent to which midwifery clinical teaching roles described in the literature strengthened the university/health service partnership 13 .…”
Section: Background Description Of the Midwifery Academic Role In The...mentioning
confidence: 99%
“…Based on student reports, it was found that they described expressions of gratitude for the contribution of midwife receptors that awakened students with examples of kindness, patience, generosity, and clinical expertise. (Doherty, 2015) Preceptors should focus on their professional role in providing unit-oriented, evidence-based skills-related learning opportunities for the preceptee while in the (Susanti, Wirakusumah and Garna, 2016) Engaged and committed receptors are critical to the success of midwifery students in a positive clinical practice experience (Griffiths et al, 2019). According to Halfer (2007), the role of the Preceptor must have responsibilities as Role Modeling, Skill Building, Critical Thinking, and Socialization.…”
Section: Role Of Preceptorsmentioning
confidence: 99%
“…Students identify a lack of opportunities in the clinical setting to raise concerns that also require further consideration. (Griffiths et al, 2019) Student midwives saw several examples of preceptors or other professionals using EBP to discuss different approaches to maternal care. (Thompson, et al, 2019).…”
Section: Preceptorship Barriersmentioning
confidence: 99%
See 1 more Smart Citation